Exploring the qualities and adaptive professional capabilities required of physicians for disaster response through perspective transformation among physicians in Fukushima, Japan - Megumi Yasuda; Rintaro Imafuku; Kaho Hayakawa; Maham Stanyon; Takuya Saiki (Frontiers in Medicine, 2026)
Background The Great East Japan Earthquake and the Fukushima Daiichi Nuclear Power Plant accident confronted health care professionals with profound uncertainty and ethical dilemmas. However, it remains unclear how physicians made sense of these extreme experiences, reconsidered their assumptions, values and professional roles, and came to recognize and embody the qualities and adaptive professional capabilities required for disaster response. Aim Through the narratives of physicians in Fukushima, Japan, this study explores the qualities and adaptive professional capabilities required for disaster response, the processes through which they are formed, and how changes interpreted through the lens of perspective transformation are reflected in later professional practice. Methods Semi-structured interviews were conducted with 15 physicians who experienced the Great East Japan Earthquake in Fukushima Prefecture, Japan. Interview transcripts were analyzed using inductive thematic analysis and interpretation informed by transformative learning theory. Hoggan’s three dimensions of transformation (depth, breadth, and relative stability) guided evaluation of the reported changes. Results Physicians described confusion and conflict when confronted with situations lacking definitive answers or when professional responsibilities clashed with personal safety. These experiences prompted dialogue and critical reflection on their values and professional roles, consistent with disorienting dilemmas. Through this process, they recognized essential qualities and adaptive professional capabilities for disaster response, including crisis-oriented communication and collaboration, applying a comprehensive community-oriented perspective, recognition of one’s role and limits and selection of optimal action, embracing diverse values and contextual backgrounds, and responsiveness to uncertainty with flexible adaptability. Participants described shifts from viewing risk communication as one-way information transmission to understanding it as dialogue, and from focusing solely on individual patients to engaging with the community as a whole. Participants described these changes as continuing to inform their subsequent clinical and educational practice. Conclusion Participants described changes in their values and professional identity that were interpreted as consistent with perspective transformation. The qualities and adaptive professional capabilities formed through reflection and dialogue under extreme circumstances became internalized in practice. These findings suggest the need to design medical education that treats uncertainty and ethical dilemmas as core learning opportunities supporting adaptive professional capabilities and ongoing professional growth.